Reconstructing Narrative Coherence in EFL Writing: A Cognitive-Rhetorical Framework for Event Causality Mapping, Referential Consistency, and Affective Trajectory Control - Margaret Stevani; Alexander Adrian Saragi (English Department of Faculty of Tarbiyah and Teacher Training, 2025)
This study investigated narrative coherence in English as a Foreign Language (EFL) writing through a cognitive-rhetorical framework that integrated event causality mapping, referential consistency, and affective trajectory control. Conducted at two private universities in North Sumatra, the study involved 24 third-year EFL students enrolled in academic writing courses. Using discourse analysis of student narratives and targeted revision tasks, the study revealed frequent disruptions in logical event sequencing, inconsistent referent tracking, and unstable emotional flow. Findings indicated that guided instruction using cognitive-rhetorical strategies significantly enhanced students’ ability to construct coherent narratives. The proposed framework supported deeper rhetorical awareness and cognitive control in written storytelling. It offered practical implications for EFL pedagogy in Indonesian university contexts.